An in vitro evaluation of fracture resistance strength of different post systems in endodontically treated teeth - Shabna Moyin; Saurabh Chaturvedi; Nasser M Alqahtani; Mansoor Shariff; Adel M Abdelmonem; Mohammed A Alfarsi (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aimed to evaluate the fracture resistance strength of different post systems in endodontically treated teeth. Materials and Methods: Freshly extracted 60 single-rooted first premolars were selected for this study. Conventional step-back technique was used to prepare a canal for all the teeth. Obturation was carried out and post space was created using a Peeso reamer. All teeth were randomly divided into three groups of 20 samples in each group: Group I, teeth inserted with prefabricated carbon posts; Group II, teeth inserted with prefabricated zirconia posts; and Group III, teeth inserted with prefabricated everStick posts. Core buildup was performed using light-cured composite resin. Compressive load required to fracture the tooth was measured using a universal testing machine. Results: The compressive strength of zirconia posts was highest with a mean of 796.10±20.78 followed by carbon posts (628.22±18.11) and lower compressive strength was exhibited by everStick posts (534.13±19.98). An analysis of variance revealed a statistically highly significant difference (P < 0.005) among the different posts used, and a statistically significant difference between carbon posts vs. zirconia posts, carbon posts vs. everStick posts, and zirconia posts vs. everStick posts (P < 0.05). Conclusion: Zirconia posts show the maximum fracture resistance than the carbon posts and everStick posts.